1994
DOI: 10.1088/0953-8984/6/26/017
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of pyridinium perchlorate

Abstract: Polycrystalline pyridinium perchlorate has been studied over a wide range of temperatures by differential thermal analysis, proton NMR spectra and relaxation, and dielectric permittivity measurements. Two solid-solid phase transitions at 232 and 248 K have been revealed and the pyridinium cation reorientations in all three phases characterized. The higher transition appears to be the Curie point of a new ferroelectric compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
71
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 9 publications
5
71
1
1
Order By: Relevance
“…Recently discovered ferroelectric properties of pyridinium tetrafluoroborate C 5 H 6 N BF À 4 abbreviated as PyBF 4 [1] were also detected in other pyridinium salts [2,3]. A characteristic feature of this new ferroelectric family is the occurrence of a sequence of two-phase transitions; in PyBF 4 there are the ferroelectric phase transition at T 1 238X7 K and another transition at T 2 204 K. Earlier NMR studies of pyridinium salts [4 to 7] proved the occurrence of reorientation of both pyridinium cation and BF 4 anion in the symmetric high-temperature phases.…”
Section: Introductionmentioning
confidence: 93%
“…Recently discovered ferroelectric properties of pyridinium tetrafluoroborate C 5 H 6 N BF À 4 abbreviated as PyBF 4 [1] were also detected in other pyridinium salts [2,3]. A characteristic feature of this new ferroelectric family is the occurrence of a sequence of two-phase transitions; in PyBF 4 there are the ferroelectric phase transition at T 1 238X7 K and another transition at T 2 204 K. Earlier NMR studies of pyridinium salts [4 to 7] proved the occurrence of reorientation of both pyridinium cation and BF 4 anion in the symmetric high-temperature phases.…”
Section: Introductionmentioning
confidence: 93%
“…Depending on their symmetry and the size of anions, these compounds exhibit a large variety of interesting phenomena: phase transitions, ferroelectricity, dynamic orientational disorder of pyridinium cations, etc., [1][2][3][4]. The ferroelectric state was observed in pyridinium tetrafluoroborate PyHBF 4 (C 5 H 5 NHBF 4 ) [1], pyridinium perchlorate PyHClO 4 [2], pyridinium perrhenate PyHReO 4 [3], and pyridinium periodate PyHIO 4 [4]. Interest in studying the latter two compounds listed above is connected with the fact that their Curie temperatures are close to room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridinium perchlorate (PClO) and pyridinium fluoroborate (PFB) are particularly interesting as they exhibit successive structural phase transitions. Single crystals studies revealed two successive phase transitions at 248 K, 232 K for PClO [6] and 240 K, 205 K for PFB [7], respectively. On descending temperature the successive phases can be numbered as I, II, and III.…”
Section: Introductionmentioning
confidence: 99%